The nuclear transcription factor Rtg1p functions as a cytosolic, post-transcriptional regulator in the methylotrophic yeast Pichia pastoris - Dey, Trishna (J Biol Chem, 2018)
Rtg1p and Rtg3p are two basic helix–loop–helix, retrograde transcription factors in the budding yeast Saccharomyces cerevisiae. Both factors heterodimerize to activate the transcription of nuclear genes in response to mitochondrial dysfunction and glutamate auxotrophy, but are not well characterized in other yeasts. Here, we demonstrate that the Rtg1p/Rtg3p-mediated retrograde signaling pathway is absent in the methylotrophic yeast Pichia pastoris. We observed that P. pastoris Rtg1p (PpRtg1p) heterodimerizes with S. cerevisiae Rtg3p and functions as a nuclear, retrograde transcription factor in S. cerevisiae, but not in P. pastoris. We noted that P. pastoris Rtg3p lacks a functional leucine zipper and interacts with neither S. cerevisiae Rtg1p (ScRtg1p) nor PpRtg1p. In the absence of an interaction with Rtg3p, PpRtg1p has apparently acquired a novel function as a cytosolic regulator of multiple P. pastoris metabolic pathways, including biosynthesis of glutamate dehydrogenase 2 and phosphoenolpyruvate carboxykinase required for the utilization of glutamate as the sole carbon source. PpRtg1p also had an essential role in methanol metabolism and regulated alcohol oxidase synthesis and was required for the metabolism of ethanol, acetate, and oleic acid, but not of glucose and glycerol. Although PpRtg1p could functionally complement ScRtg1p, ScRtg1p could not complement PpRtg1p, indicating that ScRtg1p is not a functional PpRtg1p homolog. Thus, PpRtg1p functions as a nuclear, retrograde transcription factor in S. cerevisiae and as a cytosolic, post-transcriptional regulator in P. pastoris. We conclude that PpRtg1p is a key component of a signaling pathway that regulates multiple metabolic processes in P. pastoris.